Long-term efficacy and immunopersistence of an Escherichia coli-produced HPV-16/18 bivalent vaccine: an observational extension study following a randomised, double-blind Phase III clinical trial cohortResearch in context - Fanghui Zhao; Qi Chen; Chao Zhao; Lingling Nie; Shangying Hu; Jian Yin; Lingxian Qiu; Zhaofeng Bi; Jiali Quan; Yufei Li; Mingzhu Li; Xun Zhang; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: A safe and highly efficacious Escherichia coli-produced HPV-16/18 bivalent vaccine (Cecolin®) offers a cost-effective cervical cancer prevention measure. Here, we report data on the long-term efficacy and immunopersistence up to 10 years post-vaccination. Methods: In the Phase III clinical trial (NCT01735006), 7372 women were enrolled and randomly assigned to receive the HPV or control vaccine (hepatitis E vaccine). Women from 2 sites (Xinmi City and Fengning County; N = 1986) were invited to participate in the extension study. Cervical samples were collected for ThinPrep Pap tests and HPV DNA testing. Serum samples from participants in the immune persistent subcohort (N = 300) were collected for neutralising antibody testing. The co-primary outcomes were high-grade cervical, vulvar or vaginal lesions and persistent infection (over 6 months) associated with HPV 16/18 in the per-protocol population. Findings: A total of 1648 women participated in the extension study (806 from the vaccine group and 842 from the control group). Over a median 10.2-year follow-up, vaccine efficacy was 87.5% (95% CI 6.4–99.7) against high-grade cervical, vulvar or vaginal lesions (1 case in the vaccine group and 8 cases in the control group, P = 0.0391), and 97.0% (95% CI 78.9–100.0) against persistent infection (over 6 months, 1 case in the vaccine group and 32 cases in the control group, P < 0.0001) in the per-protocol population. The GMCs of neutralising antibodies peaked by month 7, declined through month 42, with HPV-16 plateauing and HPV-18 continuing to decline thereafter. At 114 months, 98.9% (93/94) of baseline seronegative participants remained seropositive for HPV-16 with the GMC of 61.84 IU/mL and 97.0% (98/101) remained seropositive for HPV-18 with the GMC of 18.73 IU/mL. Interpretation: The E. coli-produced HPV 16/18 bivalent vaccine elicits sustained antibody responses and confers durable protection against HPV 16/18 associated high-grade cervical, vulvar or vaginal lesions and persistent infections for a minimum of 10 years post-vaccination. Funding: National Key Research and Development Program of China (2023YFC2307602), National Natural Science Foundation of China (823B2086, 82273640), Beijing Natural Science Foundation (L244091), and Fundamental Research Funds for the Central Universities (20720220005).